Efficacy of a Tobacco Quitline in Active Duty Military and TRICARE Beneficiaries: A Randomized Trial. Issue 8 (1st August 2015) - Klesges, Robert C.; Ebbert, Jon O.; Talcott, G. Wayne; Thomas, Fridtjof; Richey, Phyllis A.; Womack, Catherine; Hryshko-Mullen, Ann; Oh, John
ABSTRACT: A higher proportion of military personnel than civilians smoke cigarettes. Few randomized trials of tobacco use interventions have been conducted in the U.S. military. We evaluated the efficacy of a tobacco quitline (QL) in 1298 active duty military personnel, their dependents, reservists, and retirees who smoke cigarettes. Participants were randomized to either a proactive (counselor-initiated) or reactive (participant-initiated) QL intervention for 8 weeks. The proactive condition included up to an 8-week supply of free nicotine replacement therapy, and the reactive condition included a 2-week supply. The primary outcome was 12-month smoking abstinence. The enrolled population was predominantly affiliated with the Air Force and Army. At the end of treatment, proactive treatment was associated with a greater odds of both prolonged (44.22% vs. 24.96%; odds ratio [OR] = 2.4, P < 0.0001) and 7-day point prevalence (49.92% vs. 28.20%; OR = 2.5, P < 0.0001) smoking abstinence, a difference that was maintained for prolonged smoking abstinence at 12 months (22.03% vs. 13.41%; OR = 1.8, P < 0.0001). Our findings provide evidence that a proactive QL with nicotine replacement therapy is highly efficacious among Air Force and Army active duty and TRICARE beneficiaries and would provide an effective telephonic treatment option for this population of smokers.